Pengaruh Bias Perilaku Terhadap Keputusan Investasi Trader Aktif Generasi Z Di Indonesia Dengan Persepsi Risiko Sebagai Variabel Mediasi - Anisya Dwi Deviyanti; Vicky Oktavia; Dwi Eko Waluyo; Pradana Jati Kusuma (JEMAP, 2026)
This study aims to examine and analyze the influence of behavioral biases consisting of Overconfidence Bias, Disposition Effect, and Herding Bias on investment decisions, with risk perception as a mediating variable. The focus of this research is on Generation Z active investors in Indonesia who exhibit intensive trading characteristics in the capital market. This study employs a quantitative approach using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method through SmartPLS software. Data were collected from 165 respondents through an online questionnaire using purposive sampling technique.The results indicate that Overconfidence Bias (0.290), Disposition Effect (0.409), and Herding Bias (0.267) have a positive and significant effect on risk perception. Furthermore, risk perception is proven to have a highly dominant positive effect on investment decisions (0.734) with an effect size (f²) value of 1.167, categorized as a large effect. The mediation test confirms that risk perception plays a significant mediating role for all behavioral biases toward investment decisions, where Disposition Effect records the largest indirect effect (0.300). Overall, the research model demonstrates moderate predictive power with an Adjusted R-Square value of 0.521 for investment decisions. These findings emphasize that the psychological mechanisms of young investors in processing risk serve as the primary determinant driving their investment activities amid market volatility.